2014
DOI: 10.3201/eid2012.141026
|View full text |Cite
|
Sign up to set email alerts
|

MERS Coronavirus Neutralizing Antibodies in Camels, Eastern Africa, 1983–1997

Abstract: To analyze the distribution of Middle East respiratory syndrome coronavirus (MERS-CoV)–seropositive dromedary camels in eastern Africa, we tested 189 archived serum samples accumulated during the past 30 years. We identified MERS-CoV neutralizing antibodies in 81.0% of samples from the main camel-exporting countries, Sudan and Somalia, suggesting long-term virus circulation in these animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
275
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(295 citation statements)
references
References 13 publications
(25 reference statements)
7
275
1
7
Order By: Relevance
“…1,9,27,44 Despite the high prevalence of MERS-CoV in camels, viral transmission from camels to humans appears to be limited, and multiple countries with seropositive camels have yet to detect MERSCoV infections in humans. 18,32,49 …”
Section: Human Mers-cov Infectionsmentioning
confidence: 99%
“…1,9,27,44 Despite the high prevalence of MERS-CoV in camels, viral transmission from camels to humans appears to be limited, and multiple countries with seropositive camels have yet to detect MERSCoV infections in humans. 18,32,49 …”
Section: Human Mers-cov Infectionsmentioning
confidence: 99%
“…The present evidence suggests that camels in the Middle East, which originated from the Horn of Africa region, serve as a possible primary source of MERS-CoV infection in humans; serological evidence of the early circulation of MERS-CoV in camels in the African region and the KSA dated back to 1983 and 1992, respectively 52,20 .…”
Section: Dromedary Camelsmentioning
confidence: 98%
“…Nonetheless, several epidemiological studies have demonstrated the widespread of MERS-CoV in dromedary camels (Camelus dromedarius) in Africa and the Arabian Peninsula as early as 1983 and 1993, respectively [6,7]. Furthermore, other studies have provided strong evidences of MERS-CoV transmission from camels-to-humans [8][9][10], suggesting that dromedaries are most likely the reservoir host for MERS-CoV and an important source of human infections.…”
Section: Introductionmentioning
confidence: 99%